Women’s Rights as Propounded by Fatima Jinnah (The Pakistan Development Review, 2003)
During the years (1937-1947) when Pakistan movement was at its peak, Fatima Jinnah’s role was nothing less than a beacon of hope for the Muslim women. Though the guidance of her elder brother Quaid-i-Azam Muhammad Ali Jinnah, she herself became a role model not only for the Muslims women of South Asia, but for the women of whole Asian society. Her role as a women leader was even more important when after the death of Quaid-i-Azam in 1948 she became the focal point for aspirations of Pakistani women. It was under very difficult circumstances that she worked for the promotion of women’s rights and privileges in Pakistan.